2002
DOI: 10.1590/s1517-74912002000300003
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic biomonitoring of Brazilian dentists occupationally exposed to low doses of X-radiation

Abstract: Exposure to X-rays (ionizing radiation) may cause chromosomal aberrations (CA) in somatic or germinative cells in exposed individuals, and may lead to manifestations of diseases such as cancer. This study was carried out to assess the CA frequency in lymphocytes obtained by means of temporary culture of peripheral blood from dentists in Londrina, Paraná, Brazil, who have worked for more than ten years with X-rays. The results obtained from the experimental group were compared with a matched negative control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
3
2
1
Order By: Relevance
“…Movafagh et al in their study on radiotherapy workers found that neither age, sex or duration of exposure were significant predictors of chromosomal aberrations [20]. Miyaji and Mara in their cytogenetic study of dentist occupationally exposed to low doses of X radiation found no association between the confounding factors age and sex and the frequency of chromosomal aberrations [21]. The reason for obtaining not so significant results could be due to small sample size and limited age range in our study.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Movafagh et al in their study on radiotherapy workers found that neither age, sex or duration of exposure were significant predictors of chromosomal aberrations [20]. Miyaji and Mara in their cytogenetic study of dentist occupationally exposed to low doses of X radiation found no association between the confounding factors age and sex and the frequency of chromosomal aberrations [21]. The reason for obtaining not so significant results could be due to small sample size and limited age range in our study.…”
Section: Discussioncontrasting
confidence: 59%
“…A small number of breaks remain unrepaired and become visible in subsequent metaphase chromosomes. Several studies performed using cytogenetic analysis, report the presence of increased frequencies of chromosomal aberrations in peripheral blood lymphocytes of individuals accidentally, environmentally or occupationally exposed to cumulative low level of ionizing radiation [3][4][5]. However, the relationship between ionizing radiation exposure level and the elevation of the frequencies of different types of structural chromosomal aberrations is not yet completely clarified.…”
Section: Introductionmentioning
confidence: 99%
“…29 Significant cytogenic changes were not observed in a study conducted on blood samples of dentists exposed to low doses of ionizing radiation. 30 In the present study too, the MN cells frequency in the risk group was not significantly different from the control group. Routine radiation protection measures are followed in the area where this study was carried out.…”
Section: Discussioncontrasting
confidence: 42%
“…Cases of radiogenic dermatitis and malignancies of the hand have been reported, and a greater incidence of thyroid cancer and melanoma and greater mortality from cardiovascular diseases have been observed. In addition, cytogenetic analyses have been carrie out to observe the possible mutations in the somatic cells of dentists, but no significant differences in chromosomal aberrations were found.…”
mentioning
confidence: 99%